Measuring macrofungal biodiversity quality using two different survey approaches: A case study in broadleaf Mediterranean forests. (February 2018) - Ambrosio, Elia; Mariotti, Mauro Giorgio; Zotti, Mirca; Cecchi, Grazia; Di Piazza, Simone; Feest, Alan
Highlights: Alpha-diversity indices derived from macrofungal field surveys. Multiple surveys versus a single survey per year. Evaluation of sampling effort between survey regimens. Comparing biodiversity quality (species richness, population, evenness/dominance and sampling efficiency) between sites. Quick field methodologies for monitoring cryptic organisms. Abstract: Macrofungi represent one of the most difficult taxonomic groups of organisms to study and monitoring the diversity over time and space often requires a high field sampling effort. Two different monitoring approaches were used to assess macrofungal biodiversity in broadleaf Mediterranean forests in order to determine whether different sampling efforts can provide statistically similar diversity indices. Despite the different number of field visits, the results obtained show that some biodiversity indices (e.g. Shannon index, Eveness, Simpson index) values do not seem to be significantly affected by the survey approach chosen and a single survey per year has achieved comparable results to multiple surveys. This, in a wider biodiversity context it could produce a quick field methodology to study complex taxonomic groups, such as macrofungi.